A new species of Pseudocoutierea Holthuis from the Caribbean coast of Panama (Crustacea, Decapoda, Palaemonidae), with a key to the genus - de Grave, S. (Zootaxa, 2007)
A new species of pontoniid shrimp , Pseudocoutie rea dotae sp. nov. is described from Bocas Province (Caribbe an coast of Panama ), on the basis o f a single specimen encountered on a whip-coral , Stichopathes lutken i . The new species is closely related to the eas tern Atlantic species , P. wirtzi , with which it shares th e presence of a post-hepatic tubercl e. A key to the genus is presen ted.